2022
DOI: 10.1111/rssa.12856
|View full text |Cite
|
Sign up to set email alerts
|

A New Experiment on the use of Images to Answer Web Survey Questions

Abstract: Images might provide richer and more objective information than text answers to open-ended survey questions. Little is known, nonetheless, about the consequences for data quality of asking participants to answer open-ended questions with images. Therefore, this paper addresses three research questions: (1) What is the effect of answering web survey questions with images instead of text on breakoff, noncompliance with the task, completion time and question evaluation? (2) What is the effect of including a motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As for the respondents’ evaluation with surveys asking for images, the literature is also scarce. Bosch et al (2022) found that between 12.4% and 20.0% of respondents liked answering with images, while 47.3% to 52.7% liked answering similar questions in conventional ways. Further, nearly 80% of respondents found it easy to answer in conventional ways, versus around 50% for answering by sharing images, which also resulted taking more time for participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the respondents’ evaluation with surveys asking for images, the literature is also scarce. Bosch et al (2022) found that between 12.4% and 20.0% of respondents liked answering with images, while 47.3% to 52.7% liked answering similar questions in conventional ways. Further, nearly 80% of respondents found it easy to answer in conventional ways, versus around 50% for answering by sharing images, which also resulted taking more time for participants.…”
Section: Introductionmentioning
confidence: 99%
“…The participation rates range from 10% in the study by Jäckle et al (2019) asking for photos of receipts, to 55% in the study by Bosch et al (2019a) when asking for a photo of the place where respondents are when answering the survey. Moreover, greater item nonresponse has been found when respondents had to answer by sharing images than when using conventional response formats ( Bosch et al , 2022 ; Ilic et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Bosch et al (forthcoming) used an opt‐in panel to experiment with three different answer formats to survey questions: a text response, uploading an image, or uploading an image after receiving a motivational message. Their results show that the image conditions resulted in much lower response rates, most likely due to the increased burden, or situational aspects when the image questions are asked.…”
Section: Introductionmentioning
confidence: 99%